2010
DOI: 10.1126/science.1181263
|View full text |Cite
|
Sign up to set email alerts
|

The Free-Energy Landscape of Clusters of Attractive Hard Spheres

Abstract: One sentence summary: Experiments reveal that small clusters of hard spheres with short-range attractions favor equilibrium structures determined by geometrical rules.The study of clusters has provided the most tangible link between local geometry and bulk condensed matter. But experiments have not yet systematically explored the thermodynamics of even the smallest clusters. Here we present experimental measurements of the structures and free energies of colloidal clusters in which the particles act as hard sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
422
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 286 publications
(444 citation statements)
references
References 28 publications
19
422
0
Order By: Relevance
“…The results of this calculation for N = 6, 7, 8 are in excellent agreement with the experimentally measured probabilities (Meng et al, 2010), as shown in Figure 2. The main qualitative point from these calculations and experiments is that differences in occupancy between the various clusters are primarily related to differences in symmetry, which comes into the calculation through the rotational partition function (Cates and Manoharan, 2015), see Eqn.…”
Section: B Probabilities and Comparison With The Experimentssupporting
confidence: 86%
See 2 more Smart Citations
“…The results of this calculation for N = 6, 7, 8 are in excellent agreement with the experimentally measured probabilities (Meng et al, 2010), as shown in Figure 2. The main qualitative point from these calculations and experiments is that differences in occupancy between the various clusters are primarily related to differences in symmetry, which comes into the calculation through the rotational partition function (Cates and Manoharan, 2015), see Eqn.…”
Section: B Probabilities and Comparison With The Experimentssupporting
confidence: 86%
“…There is a tremendous opportunity for theory and experiment to work together towards materials with revolutionary properties. The equilibrium probabilities of clusters at N = 6, 7, 8 vary with the structure, even though all structures at a given N have the same total depletion potential (Meng et al, 2010;Perry et al, 2012). For N = 6, the less symmetric cluster, the polytetrahedron, occurs about 24 times as frequently as the more symmetric octahedron, even though both have 3N −6 contacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triangle-like AB 3 (Fig. 3c) and tetrahedron-like AB 4 (Fig. 3d) colloidal molecules are similarly obtained by mixing trivalent (3-patch) particles and tetravalent (4-patch) particles, respectively, with monovalent particles (see Supplementary Movie 1 for all colloidal molecules).…”
Section: Assembly Of Colloidal Moleculesmentioning
confidence: 85%
“…The past decade has seen an explosion in the kinds of colloidal particles that can be synthesized 1,2 , with many new shapes, such as cubes 3 , clusters of spheres [4][5][6] and dimpled particles 7,8 reported. Because the self-assembly of these particles is largely controlled by their geometry, only a few relatively simple crystals have been made: face-centered and body-centered cubic crystals and variants 9 .…”
Section: Introductionmentioning
confidence: 99%